2013
DOI: 10.1016/j.tjog.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Is conization once following by simple hysterectomy sufficient for all clinical stage IA1 cervical squamous cell carcinoma?

Abstract: Extrafascial simple hysterectomy may be recommended for clinical T1a1 cervical SCC regardless of the pathologic risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…A similar study of MIC published in 1997 and performed by the same pathologists revealed 59.2% of residual disease in hysterectomy specimens, when previous conization margins were positive. 6 As mentioned before, a direct comparison of the results of this study with others published series has some limitations, with some studies including varying degrees of CIN and others considering only cases with microinvasion or worse as a recurrence 7,16,20,27 (Table 4).…”
Section: Discussionmentioning
confidence: 93%
“…A similar study of MIC published in 1997 and performed by the same pathologists revealed 59.2% of residual disease in hysterectomy specimens, when previous conization margins were positive. 6 As mentioned before, a direct comparison of the results of this study with others published series has some limitations, with some studies including varying degrees of CIN and others considering only cases with microinvasion or worse as a recurrence 7,16,20,27 (Table 4).…”
Section: Discussionmentioning
confidence: 93%
“…La histerectomía radical (HR) sigue siendo el procedimiento fundamental en el tratamiento del CCU y se recomienda en invasión mayor a 3 mm de un carcinoma escamocelular (37). No obstante, cuando se descubre un cáncer estadio IA durante la conización de una lesión intraepitelial de alto grado, se recomienda realizar una histerectomía simple en lugar de una radical, debido a que la última tiene mayor morbilidad pero no difiere en mortalidad para este estadio (44). Para la HR, se han planteado dos abordajes principales, por LT o por LP.…”
Section: Histerectomía Radicalunclassified